Traumatic clamshell thoracotomy closure using plates and screws - A new look for a challenging exposure: A pilot study - Bauman, Zachary M; McIlvaine, Quentin; Ude, Ndidi; Nguyen, Jonathan; Whitbeck, Sarah Ann; Sütöri, Dávid; Athas, Vincent; Seoane, Jacqueline; Saites, Constantine; Bustillo-Aruca, Veronica; Shnaydman, Ilya; Kirsch, Jordan M; et al. (Injury, 2025)
AbstractBackgroundThe clamshell thoracotomy (CST) is a rare, but lifesaving procedure often performed in austere environments. The closure of a CST is challenging and can be fraught with post-operative complications/failure resulting in debilitating chest wall instability. The recent advent of rib and sternal fixation hardware has provided additional tools possibly offering better ways to close a CST. The objective of this study was to examine the use of plates and screws to close CSTs, hypothesizing it is safe and effective, providing good functional outcomes. MethodsThis was a multi-institutional, international, retrospective review of patients undergoing CST closure with plates and screws utilized in rib/sternal fixation. Exclusion criteria included patients that died prior to hospital discharge. Exact methods for closure were left to the discretion of the operating surgeon, however plates and screws were the main foundation. Basic demographics were obtained. Outcomes of interest included number of plates used, days to closure, complications post-operatively, length of follow-up, and post-operative functional status (1=worst functional status; 5=best functional status). Descriptive statistics were reported. ResultsNineteen patients from 7 centers were included. Two patients were excluded as they died inpatient. Of the remaining 17 patients, mean age was 34.6 (±18.8) years and 82.4 % were male. 35.3 % percent were white, 41.2 % were black, and 23.5 % were Hispanic. 82.4 % suffered penetrating trauma. Median number of plates used per patient was 1 (Interquartile range (IQR) 1,3). Median time to closure was 1 day (IQR 1,2). Four patients (23.5 %) experienced post-operative complications. Mean follow-up was 197.4 (±206.4) days with all patients obtaining satisfactory chest x-rays during this time. Median functional status reported by patients at follow-up was 4 (IQR 3,5). ConclusionClamshell thoracotomy closure with plates and screws appears to be safe and effective. Most patients reported favorable long-term functional status. Level of EvidenceLevel V, Therapeutic/care management